Quality of life with anal fistula - Owen, HA (Ann R Coll Surg Engl, 2016)
INTRODUCTION: Anal fistula affects people of working age. Symptoms include abscess, pain, discharge of pus and blood. Treatment of this benign disease can affect faecal continence, which may, in turn, impair quality of life (QOL). We assessed the QOL of patients with cryptoglandular anal fistula. METHODS: Newly referred patients with anal fistula completed the St Mark’s Incontinence Score, which ranges from 0 (perfect continence) to 24 (totally incontinent), and Short form 36 (SF–36) questionnaire at two institutions with an interest in anal fistula. The data were examined to identify factors affecting QOL. RESULTS: Data were available for 146 patients (47 women), with a median age of 44 years (range 18–82 years) and a median continence score of 0 (range 0–23). Versus population norms, patients had an overall reduction in QOL. While those with recurrent disease had no difference on continence scores, QOL was worse on two of eight SF–36 domains (p<0.05). Patients with secondary extensions had reduced QOL in two domains (p<0.05), while urgency was associated with reduced QOL on five domains (p<0.05). Patients with loose seton had the same QOL as those without seton. No difference in urgency was found between patients with and without loose seton. In primary fistula patients, 19.4% of patients experienced urgency versus 36.3% of those with recurrent fistulas. CONCLUSIONS: Patients with anal fistula had a reduced QOL, which was worse in those with recurrent disease, secondary extensions and urgency. Loose seton had no impact on QOL.